Comparison of Measures to Predict Mortality and Length of Stay in Hospitalized Patients. Issue 3 (May 2019) - Liu, Jianfang; Larson, Elaine; Hessels, Amanda; Cohen, Bevin; Zachariah, Philip; Caplan, David; Shang, Jingjing
Abstract : Background: Patient risk adjustment is critical for hospital benchmarking and allocation of healthcare resources. However, considerable heterogeneity exists among measures. Objectives: The performance of five measures was compared to predict mortality and length of stay (LOS) in hospitalized adults using claims data; these include three comorbidity composite scores (Charlson/Deyo age-comorbidity score, V W Elixhauser comorbidity score, and V W Elixhauser age-comorbidity score), 3 M risk of mortality (3 M ROM), and 3 M severity of illness (3 M SOI) subclasses. Methods: Binary logistic and zero-truncated negative binomial regression models were applied to a 2-year retrospective dataset (2013–2014) with 123, 641 adult inpatient admissions from a large hospital system in New York City. Results: All five measures demonstrated good to strong model fit for predicting in-hospital mortality, with C -statistics of 0.74 (95% confidence interval [CI] [0.74, 0.75]), 0.80 (95% CI [0.80, 0.81]), 0.81(95% CI [0.81, 0.82]), 0.94 (95% CI [0.93, 0.94]), and 0.90 (95% CI [0.90, 0.91]) for Charlson/Deyo age-comorbidity score, V W Elixhauser comorbidity score, V W Elixhauser age-comorbidity score, 3 M ROM, and 3 M SOI, respectively. The model fit statistics to predict hospital LOS measured by the likelihood ratio index were 0.3%, 1.2%, 1.1%, 6.2%, and 4.3%, respectively. Discussion: The measures tested in this study can guide nurse managers in the assignment of nursing care and coordination of needed patient services and administrators to effectively and efficiently support optimal nursing care.